The role of quantitative T1 and T2 mapping for detecting minimal hepatic encephalopathy in chronic hepatic schistosomiasis patients - Xue-Fei Liu; Ke-Ying Wang; Hai-Feng Shi; Ying Li; Xin Li (PLoS ONE, 2026)
Background Minimal hepatic encephalopathy (MHE) is a frequent neurocognitive complication in chronic hepatic schistosomiasis (CHS) patients. Conventional diagnostic tools are time-consuming and influenced by education level. Quantitative MRI mapping offers a potential non-invasive biomarker for MHE, but its role in CHS remains unclear. Aim This study aimed to evaluate the diagnostic value of quantitative T1 and T2 mapping for detecting MHE in CHS patients. Methods This prospective cross-sectional observational study was conducted from August 2023 to July 2024. A total of 88 CHS patients were enrolled and divided into MHE (n = 50) and non-MHE group (n = 38). MHE was assessed using the number connection test-A (NCT-A) and digit symbol test (DST). All participants underwent 3.0T MRI with T1 and T2 mapping. Group comparisons, correlation analyses, logistic regression, and receiver operating characteristic (ROC) curve analyses were performed. Results MHE patients exhibited significantly lower T1 values across multiple brain regions, particularly the globus pallidus (all p < 0.001). T2 values showed no significant differences between groups. Multivariable regression confirmed that lower T1 values were independently associated with MHE (p = 0.009). ROC analysis demonstrated excellent diagnostic performance of globus pallidus T1 values (AUC = 0.92, 95% CI: 0.86–0.99), with sensitivity of 0.97 and specificity of 0.90. T1 values were also correlated with neuropsychological tests (NCT-A: r = −0.345, p < 0.001; DST: r = 0.232, p = 0.029). However, T2 values showed no significant group differences or diagnostic value. Conclusion Quantitative T1 mapping, rather than T2 mapping, could be used as a potential non-invasive biomarker for detecting MHE in CHS patients. This approach offers an objective complement to psychometric testing and may facilitate earlier diagnosis and monitoring of MHE progression.